Stent thrombosis and optimal duration of dual antiplatelet therapy after coronary stenting in contemporary practice - Cho, Min Soo (Korean J Intern Med, 2017)
The introduction of drug-eluting stents (DES) in the practice of percutaneous coronary intervention (PCI) has substantially reduced angiographic and clinical restenosis but is associated with an increasing propensity for very late stent thrombosis (ST). Among several clinical, lesion, or procedure-related predictors of ST, early discontinuation of dual antiplatelet therapy (DAPT) is the most important factor for DES-associated late thrombosis; therefore, the optimal duration of DAPT is a major issue to be critically considered in the current DES era. Given that the benefit and risk of longer duration DAPT should be simultaneously considered, the optimal DAPT period following DES implantation has been controversial. Several small-to-medium sized randomized clinical trials and observational registries have indicated that short-term DAPT (< 6 months) is not inferior to 12-month DAPT with fewer bleeding events, whereas prolonged duration of DAPT (> 12 months) failed to prove its superiority. However, compelling evidence from a landmark DAPT trial has clearly demonstrated the efficacy of prolonged DAPT up to 30 months in terms of preventing ST and major cardiovascular adverse events at the expense of major bleeding. In addition, coupled with various risk algorithms, a more individualized approach to balance the efficacy and safety of optimal DAPT duration has been emphasized. In this review article, we systematically summarize the cumulative evidence from key clinical studies and try to help the physician make decisions on the optimal duration of DAPT in contemporary PCI practice.